The Use of Extensive Reading Activities to Improve Junior High School Students’ Vocabulary - Nurhanifah, Sitti; Korompot, Chairil Anwar; Fauzan, Muhammad Miftah (Journal of Excellence in English Language Education, 2026)
The study seeks to determine the effectiveness of extensive reading in increasing students' vocabulary at SMP Negeri 1 Pallangga. This research employs a pre-experimental approach utilizing a one-group pre-test and post-test design, using a vocabulary test. The participants of this study are eighth-grade students of the 2024/2025 academic year, specifically class VIII 5, consisting of 37 students selected through cluster sampling. The study employs the following instruments: a vocabulary test with four categories of questions: meaning,  word class, and word use, totaling 20 items. The Wilcoxon signed-rank test results indicate a Z value of -5.077 with a p-value (Asymp. Sig. 2-tailed) of 0.000, which is lower than α = 0.05. This leads to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁). Thus, it can be concluded that extensive reading is effective in enhancing students' vocabulary at SMPN 1 Pallangga.